ANALISIS DISTRIBUSI BERAS PUBLIC SERVICE OBLIGATION (PSO) PERUM BULOG CABANG KEDIRI - Agung, Samuel (Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine the distribution scheme of PSO (Public Service Obligation) rice in Bulog Kediri. The research uses case study qualitative methods, with data collection techniques through interviews, observation. The selection of resource persons in this study used a purposive sampling technique. The resource persons in this study were the head of operations, head of procurement and distribution section at Perum Bulog Kediri Branch. The data analysis technique uses the Miles and Huberman model, namely data reduction, data presentation and conclusions. The results of this study show that the rice distribution scheme starts from the PSO section in determining the procurement of rice or unhulled rice to the warehouse for checking grain and rice to be stored and processed in the form of packaging, then segmentation targets that have been set according to needs such as Rasta social assistance (prosperous social assistance), BTPN (non-cash food assistance program) and stabilization of market prices in response to public demand and price raising to rice.